2021
DOI: 10.1038/s41598-021-84558-2
|View full text |Cite
|
Sign up to set email alerts
|

Marine cyanobacterium Spirulina maxima as an alternate to the animal cell culture medium supplement

Abstract: Serum is a stable medium supplement for in vitro cell culture. Live cells are used in stem cell research, drug toxicity and safety testing, disease diagnosis and prevention, and development of antibiotics, drugs, and vaccines. However, use of serum in culture involves concerns such as an ethical debate regarding the collection process, lack of standardized ingredients, and high cost. Herein, therefore, we evaluated the possibility of using edible cyanobacterium (Spirulina maxima), which is a nutrient-rich, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…There are no in vivo studies providing strong evidence supporting the possible antiviral properties of Spirulina. However, Spirulina inhibits the in vitro replication of several enveloped viruses, including Herpes simplex type I, human cytomegalovirus, the measles and mumps virus, influenza A, and Human immunodeficiency virus-1 virus (HIV-1) [ 45 , 81 ]. L-asparaginase (L-AsnA) is an enzyme present in the composition of Spirulina .…”
Section: Clinical Applications On Earthmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no in vivo studies providing strong evidence supporting the possible antiviral properties of Spirulina. However, Spirulina inhibits the in vitro replication of several enveloped viruses, including Herpes simplex type I, human cytomegalovirus, the measles and mumps virus, influenza A, and Human immunodeficiency virus-1 virus (HIV-1) [ 45 , 81 ]. L-asparaginase (L-AsnA) is an enzyme present in the composition of Spirulina .…”
Section: Clinical Applications On Earthmentioning
confidence: 99%
“…The L-AsnA enzyme, contained in Spirulina, in a recent study, showed an antiproliferation effect against lung cancer A549, hepatocellular carcinoma Hep-G2, and prostate cancer PC3 human cancer cell lines. Considering the antiviral and antiproliferative activity of L-AsnA against different human cell lines, it would be desirable to investigate its effects further [ 81 ].…”
Section: Applications In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Higher cell growth [49,50] Rice protein hydrolysate CHO-320 Human HepG cells Protection against oxidation stress from hydrogen peroxide [51,52] Soy peptones CHO DG44 Improved cell production [53] Wheat hydrolysates CHO Improved cell viability [54] Marine cyanobacterium Spirulina maxima Human Lung Carcinoma Improved cell viability and proliferation [55] Chlorella vulgaris extract CHO-K1 and MSC Promoted cell growth [56] Rapeseed caked CHO-C5 Promoted cell growth [57] Silk sericin hydrolysate CHO and Hela cells Improved cell growth and proliferation [58] Whey protein CHO K1 JURKAT E6. 1 Improved cell viability and proliferation [59] The matrices shown in Table 2 are those that achieved promising results in cell proliferation and viability.…”
Section: Higher Productivity Of Human Beta Interferonmentioning
confidence: 99%
“…Despite these advantages, there are currently no commercially available culture media prepared from the hydrolyzed extracts of cyanobacteria. Moreover, little research has been done to explore the potential of cyanobacteria as a raw material for the development of new culture media ( Jeong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%